A new 8-oxo-7, 8-2′deoxyguanosine nanoporous anodic alumina aptasensor for colorectal cancer diagnosis in blood and urine. Issue 18 (4th May 2021) - Pla, Luis; Sancenón, Félix; Martínez-Bisbal, M. Carmen; Bañuls, Celia; Estañ, Nuria; Botello-Marabotto, Marina; Aznar, Elena; Sáez, Guillermo; Santiago-Felipe, Sara; Martínez-Máñez, Ramón
Abstract : A new 8-oxo-dG sensor consisting of a nanoporous material capped with an aptamer is presented and validated in real serum and urine samples, with LODs ranging from 1 to 50 nM and excellent sensitivity (96/100%) and specificity (80/100%) in 60 min. Abstract : Many important human diseases, and especially cancer, have been related to the overproduction of 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxo-dG). This molecule is a product of oxidative stress processes over nucleophilic bases in DNA. In this work, an aptasensor for the rapid, selective and accurate detection of this oncomarker is presented. The aptasensor consists of a nanoporous anodic alumina material loaded with a dye and is functionalized with an aptamer-based "molecular gate". In the presence of target 8-oxo-dG, the capping aptamer displaces from the surface due to the high affinity of the analyte with the capping aptamer, thus inducing delivery of the preloaded fluorescent dye. In contrast, in the absence of 8-oxo-dG, a poor payload delivery is accomplished. This aptamer-based nanodevice has great sensitivity for 8-oxo-dG, resulting in a LOD of 1 nM and a detection time of ca. 60 min. Moreover, the aptasensor is able to accurately detect 8-oxo-dG in unmodified urine and serum without pre-concentration treatments. This diagnostic tool is validated in a set of 38 urine and serum samples from patients diagnosed of colorectal cancer and control patients. These samples are also analyzed using a standardized and specific ELISA kit. The aptasensor displays excellent sensitivity (95.83/100%) and specificity (80/100%) for 8-oxo-dG detection in serum and urine samples, respectively. Our results may serve as a basis for the development of generalized fluorogenic diagnostic platforms for the easy diagnosis of cancer in biofluids as well as for monitoring therapeutic treatments and detection of relapses without the use of expensive equipment or trained personnel.